Aumentos de peso de la vaca lechera durante su periodo seco - Maltos, J.; Roux, H; Alba, Jorge de. (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
Daily weight gains of Criollo cows on pastures during their dry period were tabulated at Turrialba. Greatest gains were recorded during the period May to July. This is not the period of heaviest rainfall. It is suggested that the months with larger precipitation coincide with the maturity of the grasses. A correction factor would appear necessary for month of calving even though pastures remain green the year around